Employing a Socio-Technical System Approach in Prospective Life Cycle Assessment: A Case of Large-Scale Swedish Sustainable Aviation Fuels - Lai, Yat Yin; Karakaya, Emrah; Björklund, Anna (Frontiers in Sustainability, 2022)
Ambitious fossil-free targets imposed on the aviation industry worldwide demand a large volumetric supply of sustainable aviation fuel (SAF) to meet. Sweden’s commitment to a 30% volume SAF blending target by 2030 attracts interest in local production. However, the sustainability of local production is largely unknown. Addressing this gap, we aim to explore potential SAF technology pathways and assess their environmental performances in Sweden. To do so, we utilize a socio-technical system (STS) approach for pathways selection and prospective life cycle assessment (LCA) for environmental impact assessment. As a result, we identify two lignocellulosic-based and two electrofuel-based pathways and evaluate their global warming potential, mineral depletion potential, ionising radiation, land use, freshwater ecotoxicity and human toxicity impact in comparison to jet fuel. Our findings show that the well-to-wake global warming potential (100 years) of 30% SAF is on average 20% lower than that of jet fuel, with non-carbon dioxide species emitted in flight being the major contributors, prompting the need for urgent research efforts to mitigate their potential impacts. Under the assumption that no burdens are allocated to waste material used as feedstock, lignocellulosic-based 100% SAF has a well-to-pump climate impact (100 years) ranging from 0.6 to 1.5g CO2-eq/MJ compared to jet fuel’s 10.5g CO2-eq/MJ. In contrast, the well-to-pump climate impact (100 years) of electrofuel-based 100% SAF (ranging from 7.8 to 8.2g CO2-eq/MJ) is only marginally lower than that of jet fuel, mainly attributed to emissions from steel and concrete produced for wind turbine manufacturing. In general, the use of electricity generated by wind power could shift the potential environmental burden associated with jet fuel from global warming to mineral depletion, land use, freshwater ecotoxicity and human toxicity. The STS approach underscores the need to prioritize changes in systems underpinning SAF production, in turn supporting policy and investment decision making.